Pengaruh Pijat Oksitosin terhadap Breast Engorgement pada Ibu Post Partum - Claudia Banowati Subarto; Riska Yasmin (Borneo Nursing Journal (BNJ), 2025)
Background: Breast engorgement is a common issue among postpartum mothers, characterized by swelling, pain, and firmness in the breasts. It occurs due to inadequate breast emptying. If left untreated, this condition can progress to mastitis, breast abscesses, and early cessation of breastfeeding. Oxytocin massage is believed to accelerate milk let-down and reduce pain. Non-pharmacological methods for managing breast engorgement include warm compresses, breastfeeding education, and oxytocin massage techniques. Objective: To compare the effectiveness of oxytocin massage with standard breast care in reducing breast engorgement among postpartum mothers. Methods: A randomized controlled trial was conducted with 30 postpartum mothers, evenly divided into an oxytocin massage intervention group and a control group receiving warm compresses and education. The intervention consisted of 15-minute sessions twice daily for 3 days. Engorgement scores were measured before and after interventions in both groups. Wilcoxon signed-rank tests were used for within-group analysis, and the Mann–Whitney test was used for between-group comparisons. Results: The intervention group showed a decrease in median engorgement score from 4 to 1 (p < 0.001), whereas the control group’s score reduced from 4 to 2 (p = 0.02). Between-group comparison revealed a significantly greater effect of massage (p = 0.004). The massage group also reported greater reductions in pain and improved breastfeeding comfort. Conclusion: Oxytocin massage is significantly more effective than standard care in reducing postpartum breast engorgement and pain. It is recommended that this technique be integrated into midwifery practice as a non-pharmacological intervention to support breastfeeding and maternal well-being.